can someone help me do this expression 6+(8÷2)-2+(4-1)
Divide first 8 and 2 and subtract 4 - 1
[tex] \large \sf = 6 + 4 - 2 + (4 - 1)[/tex]
[tex] \large \sf = 6 + 4 - 2 + 3[/tex]
Lastly calculate the sum or difference
[tex] \sf \: calculate \: the \: sum \: of \: the \: positive \: numbers \: \: \large \sf \rightarrow \red{6 + 4} - 2 \red{+ 3}[/tex]
[tex] \large \sf = 13 - 2[/tex]
[tex] \large \sf = 11[/tex]
[tex] \huge \orange{ \underline{ \boxed{11}}}[/tex]
HOPE THIS HELP YOU! HAVE A NICE DAY!
~kimtaetae92~